150 mW Tb3+ doped chalcogenide glass fiber laser emitting at λ > 5 μm. (June 2023) - Koltashev, V.V.; Denker, B.I.; Galagan, B.I.; Snopatin, G.E.; Sukhanov, M.V.; Sverchkov, S.E.; Velmuzhov, A.P.; Plotnichenko, V.G.
Highlights: Five microns chalcogenide glass fiber laser. Terbium laser with 150 mW output. Self Q-switching of terbium fiber laser. Abstract: The paper describes terbium-doped chalcogenide glass fiber lasers emitting up to 150 mW at 5.1–5.4 μm under CW pumping by a thulium 1.908 µm fiber laser. Attention is drawn to the temporal dynamics of their radiation and to its dependence on the doping level.